(untitled) (Annals of Medical Research, 2025)
Aim: To evaluate the effect of preeclampsia on corneal tomography and specular microscopy parameters. Materials and Methods: A total of 22 preeclamptic women were evaluated prospectively. Patients were evaluated at prepartum and postpartum third months. Best-corrected visual acuity (BCVA), intraocular pressure (IOP), slit lamp, optical coherence tomography, corneal tomography, and specular microscopy were recorded and compared. Results: Prepartum BCVA was 0.065±0.638 logMAR, and postpartum BCVA was 0.050±0.823 logMAR, which was significantly different (p=0.033). The mean spherical equivalent was -0.68±1.27 diopter at prepartum and 0.00±1.41 diopter at postpartum period (p<0.001). While prepartum IOP was 16.90±2.92 mmHg, post-partum IOP was 15.40±3.17 mmHg (p=0.041). No significant changes were detected between the prepartum and postpartum period in terms of flat keratometry, steep keratometry, average keratometry, max keratometry, topographic astigmatism, and mean corneal endothelial cell density (ECD). The mean ACV (p=0.012), ACD (p=0.035), and ACA (p=0.032), the mean coefficient variation (CV) (p=0.030) were significantly lower at postpartum period (p=0.032). The percentage of hexagonal cells (HEX) increased (p=0.008) at postpartum period. The mean CCT was 572.81±66.79μm in the prepartum period and 553.90±51.51μm in the postpartum period (p=0.039). Conclusion: This study indicates that preeclampsia affects corneal cell morphology including CV and HEX, and significant changes in BCVA, IOP, and CCT postpartum. Depending on the change in IOP, it may suggest that the ocular hypotensive effect of pregnancy may have been eliminated by preeclampsia. However, no significant differences were found in corneal topography parameters. Further long-term studies with larger patient cohorts are needed to determine whether these effects are persistent and clinically significant.